Personnel management information system in order to create up-to-date and integrated personel data and information in the personnel and human resources agency in malaka regency - Rahu, Kristina Yunita de; Neolaka, Melkisedek N.B.C.; Djaha, Ajis Salim Adang (Journal of Multidisciplinary Academic and Practice Studies, 2023)
Purpose: This study discusses the personnel management information system to create up-to-date and integrated personnel data and information in the Personnel and Human Resources Development Agency in Malaka Regency. Research Methodology: This study used a qualitative approach. Data collection methods for this research will be conducted through interviews, observations, and document searches. The data analysis technique used in this study is based on the theory of Miles and Huberman. Results: The findings reveal that the implementation of SIMPEG in Malaka Regency remains ineffective. Personnel data management still relies heavily on manual (paper-based) and Excel systems, leading to delays, inaccuracies, and unintegrated databases. Problems include mismatches between BKPSDM records and the State Civil Service Agency (BKN) system, resulting in canceled promotions, delayed pension processing, and the inappropriate placement of civil servants. Major inhibiting factors include limited budget allocations, the absence of a permanent building and adequate IT infrastructure, and insufficient human resources with IT expertise. Conclusions: The study concludes that SIMPEG has yet to be effectively realized in Malaka Regency, causing inefficiency, inaccuracies, and poor service delivery in personnel management. Limitations: Researchers find it difficult to make more detailed observations; therefore, they cannot display more related data and information. Contribution: This research can serve as a scientific basis for evaluating the application of the personnel information system at the Personnel and Human Resources Development Agency of Malaka Regency. In addition, this research can provide scientific information for students of Public Administration Science.